Setting Priorities: Demonstrating Stakeholder Value Networks in SysML. Issue 1 (16th August 2018) - Sease, Matthew; Smith, Brian; Selva, Daniel; Hummell, James
Abstract: Graph theory is used across systems science and engineering to obtain insights about the structure of complex systems. For example, in Stakeholder Value Networks (SVN), graphs are used to model stakeholders and their value exchanges. Centrality measures can thus be used to help the systems engineer prioritize among stakeholder needs. SVN have documented utility across multiple applications. The purpose of this paper is to demonstrate a relatively simple technique to codify an SVN within a Systems Modeling Language (SysML) based tool. Such a technique enables the prioritization of stakeholders to permeate the entire system model. The authors constructed a SysML model of a fictitious enterprise to demonstrate the SVN method. Stereotypes and tag values were used to visualize the data created during the SVN analysis. The output of the SVN was propagated to additional system elements such as Stakeholder Needs, System Goals and System Functions. These were created by stereotyping standard SysML elements. In addition to integrating SVN with SysML, the authors show how the SVN can provide input for a trade‐off analysis.